Wilson’s disease - Saeedi, Ilyas; Rehman, Sher; Ilyas, Nusrat (Journal of Postgraduate Medical Institute, 2011)
Wilson's disease is an autosomal recessive abnoramlaity in the hepatic excretion of copper that results in toxic accumulations of the metal in liver, brain and other organs. The disease occurs in populations of every ethnic and geographical origin and has a word wide prevalence of about I in 30,000 with a carrier frequency of I in abnormal gene (the locus on the long arm of chromosome 13) is present in all racial group studied so far and a higher incidence has been noted in Arabs. Chinese, Japanese and indians.